Limited Force and the Fight for the Just War Tradition - Braun, Christian Nikolaus (Georgetown University Press, 2023)
A moral compass for the use of limited force that draws on the just war thought of Thomas AquinasOne of the most contentious developments in contemporary international relations has been the increased use of limited force. On the one hand, insofar as it signals greater constraint, the shift away from the mechanized slaughter of large-scale warfare toward more calibrated applications of force may be hailed as a step in the right direction. On the other, because uses of limited force appear more compartmentalized and therefore containable, it may encourage states' more frequent recourse to arms. How, then, are we to make moral sense of this shift toward the small-scale use of force? When are these operations morally justifiable? Limited Force and the Fight for the Just War Tradition offers a moral compass for just war theorists and extends the limited scholarship on jus ad vim (the just use of limited force). Based on a historical approach to just war and case studies, this book provides practical arguments on the question of how the practice of targeted killing and punitive airstrikes should be regulated in order to be morally defensible. Drawing from a historical reading of the just war thought of Thomas Aquinas, Braun demonstrates how classical just war thinking not only helps us grapple with the moral questions of limited force but can also make an important third-way contribution to a field of study that has been engaged in a metaphorical fight about the just war tradition.